ANALYSIS OF LANGUAGE STYLE IN THE NOVEL “RAIN” BY TERE LIYE - Marudut Bernadtua Simanjuntak; Syafa Zhafira Putriyanda (Jurnal Riset Rumpun Ilmu Bahasa, 2022)
Novels usually only contain writings and rely on the imagination of the reader to describe what happened. Writers and authors must be able to describe their imagination so that the reader can be carried away in the story. For this reason, writers and authors usually use language style to make the story more lively. Tere Liye is one of the well-known Indonesian writers who has its own characteristics in the writing style of each novel. The style of language used by each writer and author of novel will be different. In this study, it will be discussed the style of language used in the novel "Hujan" by Tere Liye. The “Hujan” novels managed to enter the ranks of the Best Seller novels when it was published. It's not only the storyline that can attract readers, but the language it uses also manages to attract people to read novels. This study uses an analytical method, namely by analyzing the contents of the novel "Hujan" by Tere Liye. This study will discuss the language styles contained in the novel “Hujan” including allegory, alusio, anticlimax, antithesis, asyndeton, hyperbole, climax, metaphor, correction, paradox, personification, pleonasm, polysyndeton, repetition, rhetoric, simile, and synecdoche.